2020
DOI: 10.1186/s13075-020-02300-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of systemic lupus erythematosus on the risk of infection after total hip arthroplasty: a nationwide population-based matched cohort study

Abstract: Background We aimed to assess the impact of systemic lupus erythematosus (SLE) on the risk of infection after total hip arthroplasty (THA). Methods We identified patients undergoing primary THA (1996–2013) in Taiwan National Health Insurance Research Database (NHIRD). Patients were then divided into the SLE and control groups according to the diagnosis of SLE. We used 1:1 propensity score to match the control to the SLE group by age, sex, and comorbidities. The primary outcome was infection, including early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 30 publications
0
22
0
1
Order By: Relevance
“…Demographics and clinical outcomes were summarized in Tables 1 Tables 2. Among the ten screened citations, seven were the case-control studies [7,11,14,15,17,23,24], two were retrospective [18,25], and one was cohort studies a study [10]. A total of 29573 hips in the SLE group were studied compared to 4013027 hips in the non-SLE group.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Demographics and clinical outcomes were summarized in Tables 1 Tables 2. Among the ten screened citations, seven were the case-control studies [7,11,14,15,17,23,24], two were retrospective [18,25], and one was cohort studies a study [10]. A total of 29573 hips in the SLE group were studied compared to 4013027 hips in the non-SLE group.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…[3]Some studies have reported several complications of total hip replacement in patients with SLE and postoperative Harris hip scores (HHS) and other functional scoring results. [7][8][9][10][11][12][13][14][15][16] At present, there is no clear consensus on the impact of complications after THA in patients with SLE. Patients with SLE undergoing THA are widely considered to have an increased risk of postoperative complications.…”
mentioning
confidence: 99%
“…Although it is generally believed that patients with systemic lupus erythematosus could have good final function after THA, controversies remain with regard to whether patients with lupus have more complications after undergoing THA. Some case-control studies have shown that SLE patients have a higher incidence of perioperative complications and longer hospital stay during the perioperative period of total hip arthroplasty than patients with rheumatoid arthritis or osteoarthritis [8][9][10][11][12][13][14]. Some studies have reported that SLE is not an independent risk factor for perioperative adverse events in THA.…”
Section: Introductionmentioning
confidence: 99%
“…3 The risk of PJI after TKA or THA has been reported to be 50-80% higher for patients with in ammatory arthritis (IA) conditions such as rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). [4][5][6] Epidemiologic studies have identi ed differences in the onset of PJI between osteoarthritis (OA) and RA patients, namely OA patients are at highest risk for PJI within the rst two years of surgery whereas the risk of PJI persists for the life of the implant in RA patients. 7 The increased risk of PJI in IA patients may be related pharmacologic immunosuppression, immune dysregulation, and/or high disease activity.…”
Section: Introductionmentioning
confidence: 99%